Self-Reported Physical Activity, Injury, and Illness in Canadian Adolescent Ski Racers - Doyle-Baker, Patricia K.; Emery, Carolyn A. (Frontiers in Sports and Active Living, 2020)
Youth ski racers spend a considerable amount of time on snow and this may detract from other activities known to influence fundamental movement skills and overall health related outcomes. Parents of racers (n = 52 F; n = 44 M; age range 9–14 years) registered in the Canadian club system completed a baseline medical questionnaire during preseason testing in 2017. We describe physical activity volume and sport participation outside of physical education classes over the previous 12 months and report on injuries, medication use and health care utilization. The mean number of activities participated was five (range 1–14) with cycling, hiking, and swimming as the preferred choice and a cumulative mean of just under 400 h of activity was reported (range F 27–1,015; M 62–869 h/year) in the past year. During the past 12 months 16% of the athletes reported being injured and injury severity impacted return to sport with range of reported days missed from 1 to 365 days. Thirteen non-concussive injuries were reported in alpine skiing and females (12%, 6/52) reported more lower limb injuries than males (7%, 3/44). More males were concussed over their lifetime, with alpine skiing accounting for 46% and mountain biking 15%. Most athletes (85%) did not take medication on a regular basis and those that did had a medical diagnosis. The frequency of respiratory conditions was 13% (12/96) with males reporting slightly more cases than females. No difference in emergency visits occurred (25%) between males and females in the past 12 months, however females reported more (n = 102) allied health care, sport medicine and x-rays appointments when compared to males (n = 65). In summary, a high volume of physical activity (an hour plus per day) over the previous 12 months was reported with racers participating in several activities outside of skiing, likely honing their fundamental movement skills. Close proximity to the mountains may have influenced their choices of activity outside of ski racing, and their injuries and a variety of health conditions were typical of their age group. Future research employing wearable technology to objectively quantify the volume and intensity of physical activity participation is recommended.